Rare coral under the genomic microscope: timing and relationships among Hawaiian Montipora - Cunha, Regina Lopes da (2019)
Background Evolutionary patterns of scleractinian (stony) corals are difficult to infer given the existence of few diagnostic characters and pervasive phenotypic plasticity. A previous study of Hawaiian Montipora (Scleractinia: Acroporidae) based on five partial mitochondrial and two nuclear genes revealed the existence of a species complex, grouping one of the rarest known species (M. dilatata, which is listed as Endangered by the International Union for Conservation of Nature - IUCN) with widespread corals of very different colony growth forms (M. flabellata and M. cf. turgescens). These previous results could result from a lack of resolution due to a limited number of markers, compositional heterogeneity or reflect biological processes such as incomplete lineage sorting (ILS) or introgression. Results All 13 mitochondrial protein-coding genes from 55 scleractinians (14 lineages from this study) were used to evaluate if a recent origin of the M. dilatata species complex or rate heterogeneity could be compromising phylogenetic inference. Rate heterogeneity detected in the mitochondrial data set seems to have no significant impacts on the phylogenies but clearly affects age estimates. Dating analyses show different estimations for the speciation of M. dilatata species complex depending on whether taking compositional heterogeneity into account (0.8 [0.05–2.6] Myr) or assuming rate homogeneity (0.4 [0.14–0.75] Myr). Genomic data also provided evidence of introgression among all analysed samples of the complex. RADseq data indicated that M. capitata colour morphs may have a genetic basis. Conclusions Despite the volume of data (over 60,000 SNPs), phylogenetic relationships within the M. dilatata species complex remain unresolved most likely due to a recent origin and ongoing introgression. Species delimitation with genomic data is not concordant with the current taxonomy, which does not reflect the true diversity of this group. Nominal species within the complex are either undergoing a speciation process or represent ecomorphs exhibiting phenotypic polymorphisms.